Fabrication of Transparent Conductive Zinc Oxide Co-Doped with Fluorine and Zirconium Thin Solid Films by Ultrasonic Chemical Pyrolysis: Effects of Precursor Solution Aging and Substrate Temperature. (8th July 2013) - Castañeda, Luis
Abstract : Highly transparent, conducting zinc oxide [ZnO] thin films co-doped with fluorine and zirconium have been deposited on glass substrates by the ultrasonic chemical spraying technique. The effects of aging of the starting solution and substrate temperature on the structural, morphological, and electrical properties of the ZnO:F:Zr films have been studied. The resistivity of the films decreases with the aging time of the starting solution until the seventeenth day reaching a minimum of about1.2 × 10 − 2  Ω cm and then increases. Though all the samples are of polycrystalline hexagonal wurtzite type and grow preferentially with (002) plane parallel to the substrate, their morphology depends strongly on the aging time of the reaction solution. The optical transmittance of all the films remained around 80% in the visible spectral range. These highly transparent, low resistive thin films are expected to be highly useful as transparent electrodes in the fabrication of thin film solar cells.